"It Hits Me Right Here at my Heart": Promoting Emotional Health of Home Care Workers. (April 2023) - Janssen, Leah M.; Abbott, Katherine M.
Demand for home and community-based services continues to outpace employment of home care workers (HCWs) who provide this vital assistance. HCWs face challenges that contribute to inadequate staff retention. Of particular concern is the lack of research on HCWs' emotional health. This research describes facilitators and resources that support HCW emotional health. Qualitative descriptive interviews were conducted with a purposive sample of HCWs ( n = 17) who were formally recognized for their success. Interviews were audio recorded, transcribed verbatim, and coded in Dedoose. Thematic analysis revealed three facilitators of emotional health that HCWs link to their professional success: "right state of mind, " practicing self-care, and a combined sense of appreciation and support. HCWs highlight specific, practicable resources that promote their emotional health. Policy implications connects low wages and benefits to HCW emotional health, and practice implications for enhancing training and support to retain these important workers.